Changes in Perceived Self-efficacy of Physical Therapist Students Following a Pediatric Experiential Learning Opportunity. Issue 1 (January 2019) - Wolden, Mitch; Anderson, Brittany; Ray, Chris
Abstract : Purpose: Physical therapists (PT) must be competent to treat patients across the lifespan, from pediatrics through geriatrics. Increasing the amount of experiential learning (EL) in pediatrics presents an opportunity for students to improve their self-efficacy in communication and patient handling. The purpose was to investigate changes in PT students' perceived self-efficacy in communication and patient handling following a structured and focused 8-week EL opportunity with a pediatric population. Methods: Thirty-two PT students completed the Pediatric Communication and Handling Self-Efficacy Scale before and after an 8-week pediatric EL opportunity. A paired-samples t test was performed to assess changes in students' self-efficacy levels of communication and patient handling. Results: Perceived self-efficacy levels significantly improved in regard to students' communication and patient handling skills following a pediatric EL opportunity. Conclusions: Our findings reinforce the benefits of incorporating pediatric EL opportunities into the DPT curriculum as an effective learning strategy in pediatric education. Abstract : Supplemental Digital Content is Available in the Text.The purpose was to investigate changes in PT students' perceived self-efficacy in communication and patient handling following a structured and focused clinical opportunity with a pediatric population.